Peculiarities of the fitonim’s periwinkle, poppy, mallow and in Ukrainian literature from the perspective of lingua, mental (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In this the peculiarities of the fitonim’s periwinkle, poppy, mallow and in Ukrainian literature from the perspective of lingua, mental, ways to enhance values of the fitonim’s characters. Proved that Ukrainian literature the fitonim’s its semantic structure combine traditional and innovative them.
Keywords: fitonim’s; symbol; lingua; mental